Kepastian Hukum Pelayanan Kesehatan Akupunktur Dalam Program Jaminan Kesehatan Nasional - Ivonne Jonathan; Devi Dharmawan (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: Acupuncture is a type of advanced health service which is covered by PT. Askes. Since BPJS Kesehatan applied, acupuncture is not covered by National Health Insurance (JKN) program. BPJS Kesehatan refers to Clause 25 verse (1) letter K of Presidential Regulation No.19 of 2016 concerning Second Amendment of Presidential Regulation No.12 of 2013 concerning Health Insurance. The provisions of the Minister of Health Regulation No.28 of 2014 concerning Guidelines for Implementing National Health Insurance are different from Presidential Regulations on Health Insurance which states that medical acupuncture is covered by JKN. BPJS Kesehatan uses lex superior derogate legi inferior, therefore it does not cover acupuncture in the implementation of the JKN program. This study was a normative study with a statute approach and a conceptual approach. Method: The study showed that the issue of Law No.36 of 2014 concerning Health Practitioner gives legitimacy to acupuncture in Indonesia. The Law of Health Practitioner categorizes acupuncture into physical therapy and separates it from traditional medicine. Results: The provisions in implementing regulations of BPJS Law have not referred to the position of acupuncture in Indonesia and still categorize acupuncture as complementary, alternative and traditional medicines. The settlement of acupuncture regulations disharmony in the JKN program using lex superior principle has not been sufficient because it has not been able to provide legal certainty and legal protection. Conclusion: Regulatory reformation of acupuncture in Indonesia is urgently required, especially in the JKN program, so the implementation of the legal position of acupuncture that is guided by the Law of Health Practitioner can be implemented effectively and efficiently.